We can work it out: A multilevel examination of relationships among group and individual technology workarounds, and performance - Wei, Shaobo; Chen, Xiayu; Rice, Ronald E. (Journal of Operations Management, 2023)
AbstractDespite the operational nature of enterprise system (ES) implementation and use, individual employees or work groups may deploy technology workarounds to circumvent inflexibility in or obstacles to using the ES. However, our understanding of the multilevel nature of technology workarounds and their performance implications remains limited. Drawing upon the multilevel theory of system usage and adaptive structuration theory, the current study examines the conditions under which group technology workarounds affect group performance, individual technology workarounds, and individual performance. Based on two studies with different research designs, we find that group technology workarounds have distinctive effects on short‐ and on long‐term group performance. Specifically, while the impact of group technology workarounds on group performance is significantly positive in the short term, such effect diminishes over time. System failure and competition intensity strengthen the positive effect of group technology workarounds on short‐term performance, whereas system failure and task nonroutineness lessen the negative effect of group technology workarounds on long‐term performance. Our study further confirms the multilevel nature of technology workarounds, finding that group technology workarounds can influence individual technology workarounds and thereby individual performance. Our results support the view that technology workarounds as a group action should be considered alongside individual technology workarounds, as well as their positive and negative effects on both group and individual performance, in both the short‐ and long‐term.